2017
DOI: 10.1038/leu.2017.145
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy and safety of low-dose CD19-directed CAR-T cell therapy in 51 refractory or relapsed B acute lymphoblastic leukemia patients

Abstract: Refractory or relapsed B lymphoblastic leukemia (B-ALL) patients have a dismal outcome with current therapy. We treated 42 primary refractory/hematological relapsed (R/R) and 9 refractory minimal residual disease by flow cytometry (FCM-MRD) B-ALL patients with optimized second generation CD19-directed CAR-T cells. The CAR-T-cell infusion dosages were initially ranged from 0.05 to 14 × 10/kg and were eventually settled at 1 × 10/kg for the most recent 20 cases. 36/40 (90%) evaluated R/R patients achieved comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
197
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(208 citation statements)
references
References 27 publications
10
197
1
Order By: Relevance
“…Previous reports demonstrated persistence for 19‐28z CAR‐T cells was about three months. Pan et al () observed 93·3% patients with undetectable CAR‐T19 cells in the peripheral blood on day 30 and a median 64 days for relapse after CAR‐T19 without HSCT. Therefore, we recommended bridging to allo‐HSCT after CR with CAR‐T to have more patients remaining in durable remission and the interval from CAR‐T to allo‐HSCT within two months if possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports demonstrated persistence for 19‐28z CAR‐T cells was about three months. Pan et al () observed 93·3% patients with undetectable CAR‐T19 cells in the peripheral blood on day 30 and a median 64 days for relapse after CAR‐T19 without HSCT. Therefore, we recommended bridging to allo‐HSCT after CR with CAR‐T to have more patients remaining in durable remission and the interval from CAR‐T to allo‐HSCT within two months if possible.…”
Section: Discussionmentioning
confidence: 99%
“…For refractory/relapsed B-ALL, unprecedentedly high CR rates have been reported by different centres despite differences in CAR construct and transfection methods (Davila et al, 2014;Maude et al, 2014;Lee et al, 2015;Pan et al, 2017;Pan et al, 2019), but half of the patients will relapse within one year after CAR-T therapy if not bridged to allo-HSCT (Lee et al, 2015;Gardner et al, 2018). Following CAR-T therapy, more cases could be successfully transitioned to allo-HSCT than the low frequency of about 5% for refractory/relapsed B-ALL transitioned to transplantation after salvage chemotherapy (Thomas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al had showed that the patients with relapsed/refractory Bcell malignancies showed no sign of relapse if they received CAR-T cells treatment followed by allo-HSCT at the last follow-up [23]. In personal communication, Tong also showed that the survival is better for patients with refractory/relapsed B-cells ALL who received allo-HSCT after CD19-CAR-T cells treatment compared with the patients only received CAR-T cells [24].…”
Section: Car-t Cells As a Bridge Of Allogeneic Transplantationmentioning
confidence: 95%
“…Even so, 17 (85%) of 20 were in an ongoing remission with a 1-year leukemia-free survival (LFS) of 79.5% and overall survival of 92.3%, which represents an improvement in remission durability over that seen with their single-antigen targeting treatments. 9,10 These data support the safety and feasibility of sequential CAR T-cell infusion strategies, while demonstrating evidence for dual CAR T-cell expansion and the potential for clinical benefit, leading to an improved LFS without the necessity of a consolidative HSCT.…”
Section: Timing For Infusion Of Cd22 Car T Cells Was Based On Loss Ofmentioning
confidence: 62%